Answer:
B. 2x - 3
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Distributive Property
Algebra I
- Terms/Coefficients
- Functions
- Function Notation
Explanation:
Step 1: Define
Identify
f(x) = 3x - 1
g(x) = x + 2
(f - g)(x) is f(x) - g(x)
Step 2: Find
- Substitute in functions: (f - g)(x) = 3x - 1 - (x + 2)
- [Distributive Property] Distribute negative: (f - g)(x) = 3x - 1 - x - 2
- [Subtraction] Combine like terms (x): (f - g)(x) = 2x - 1 - 2
- [Subtraction] Combine like terms: (f - g)(x) = 2x - 3